Design Challenges for Electronic Medication Administration Record Systems in Residential Aged Care Facilities - Tariq, A.; Lehnbom, E.; Oliver, K.; Georgiou, A.; Rowe, C.; Osmond, T.; Westbrook, J. (Applied Clinical Informatics, 2014)
Introduction: Electronic medication administration record (eMAR) systems are promoted as a potential intervention to enhance medication safety in residential aged care facilities (RACFs). The purpose of this study was to conduct an in-practice evaluation of an eMAR being piloted in one Australian RACF before its roll out, and to provide recommendations for system improvements.Methods: A multidisciplinary team conducted direct observations of workflow (n=34 hours) in the RACF site and the community pharmacy. Semi-structured interviews (n=5) with RACF staff and the community pharmacist were conducted to investigate their views of the eMAR system. Data were analysed using a grounded theory approach to identify challenges associated with the design of the eMAR system.Results: The current eMAR system does not offer an end-to-end solution for medication management. Many steps, including prescribing by doctors and communication with the community pharmacist, are still performed manually using paper charts and fax machines. Five major challenges associated with the design of eMAR system were identified: limited interactivity; inadequate flexibility; problems related to information layout and semantics; the lack of relevant decision support; and system maintenance issues.We suggest recommendations to improve the design of the eMAR system and to optimize existing workflows.Discussion: Immediate value can be achieved by improving the system interactivity, reducing inconsistencies in data entry design and offering dedicated organisational support to minimise connectivity issues. Longer-term benefits can be achieved by adding decision support features and establishing system interoperability requirements with stakeholder groups (e.g. community pharmacies) prior to system roll out. In-practice evaluations of technologies like eMAR system have great value in identifying design weaknesses which inhibit optimal system use.Citation: Tariq A, Lehnbom E, Oliver K, Georgiou A, Rowe C, Osmond T, Westbrook J. Design challenges for electronic medication administration record systems in residential aged care facilities: a formative evaluation. Appl Clin Inf 2014; 5: 971–987http://dx.doi.org/10.4338/ACI-2014-08-RA-0062
Keywords: Medication administration; electronic medication administration records; residential aged care facilities; system design; formative evaluation